2020
DOI: 10.1111/hepr.13476
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nakanuma staging and cytokeratin 7 staining for diagnosing recurrent primary biliary cholangitis after living‐donor liver transplantation

Abstract: Aim: Diagnosis of primary biliary cholangitis (PBC), which recurs in approximately 30% of liver transplant recipients, is histology-based, but no staging system has been established for recurrent PBC (rPBC). We used the Nakanuma staging system and cytokeratin 7 (CK7) staining to examine post-transplant liver biopsy specimens retrospectively and to evaluate histological features of rPBC.Methods: From 107 patients who underwent living donor liver transplantation for PBC, 60 recipients with 214 liver biopsies aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…44 The associations between the POR and the CK7 grading of the ductular reaction or fibrosis at pretreatment in our study were different from those in the original study by Carbone et al 24 Extension of the CK7-positive bile ductules was employed for evaluation in the original study; however, we evaluated the CK7 grading of the ductular reaction by using the semiquantitative scoring system, which is often used in clinical and basic science research. 29,45 This difference in the evaluation method and the pathological heterogeneity may influence our results. Secondly, while the American Association for the Study of Liver Diseases practice guidance 13 and the European Association for the Study of the Liver clinical practice guidelines 14 recommend UDCA at a dose of 13-15 mg/kg/day, the standard dose of UDCA for PBC recommended by the clinical practice guidelines in Japan is 600 mg/day.…”
Section: Discussionmentioning
confidence: 98%
“…44 The associations between the POR and the CK7 grading of the ductular reaction or fibrosis at pretreatment in our study were different from those in the original study by Carbone et al 24 Extension of the CK7-positive bile ductules was employed for evaluation in the original study; however, we evaluated the CK7 grading of the ductular reaction by using the semiquantitative scoring system, which is often used in clinical and basic science research. 29,45 This difference in the evaluation method and the pathological heterogeneity may influence our results. Secondly, while the American Association for the Study of Liver Diseases practice guidance 13 and the European Association for the Study of the Liver clinical practice guidelines 14 recommend UDCA at a dose of 13-15 mg/kg/day, the standard dose of UDCA for PBC recommended by the clinical practice guidelines in Japan is 600 mg/day.…”
Section: Discussionmentioning
confidence: 98%
“…As in de novo PBC, progressive fibrosis is observed in rPBC. It has been shown that the scoring and grading systems used for de novo PBC, and especially the popular Nakanuma staging system, can be applied in rPBC to evaluate disease progression and prognosis [26 ▪ ].…”
Section: Recurrence Of Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Subsequent studies have suggested that the Nakanuma system is more practical because it predicts adverse prognosis of PBC patients [75,76] and may also help to predict treatment responses [77]. Moreover, as a recent study suggested, the Nakanuma staging system and K 7 grading correlate well with recurrent PBC and disease progression after living-donor liver transplantation [78]. Bile ducts loss and K 7 score may be used as markers for progressive recurrent PBC [78].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a recent study suggested, the Nakanuma staging system and K 7 grading correlate well with recurrent PBC and disease progression after living-donor liver transplantation [78]. Bile ducts loss and K 7 score may be used as markers for progressive recurrent PBC [78]. Also, a study by Warnes et al concluded that sinusoidal fibrosis is the major histologic parameter providing independent prognostic value [79].…”
Section: Introductionmentioning
confidence: 99%